TA‘ABBUDI AND TA‘AQQULI OBJECTS IN THE DETERMINATION OF IDDAH MAINTENANCE: A NORMATIVE MAQASIDI STUDY - Rizani, Muhammad; Khasyi’in, Nuril (International Journal of Multidisciplinary Reseach, 2025)
This article examines the normative structure of iddah maintenance in Islamic family law through an integrative framework that combines classical fiqh, maqāṣid al-sharī‘ah, and Indonesian positive law. Although the Qur’an affirms the obligation to provide financial protection for women after divorce, the practice of Religious Courts in Indonesia demonstrates significant disparities in determining the amount of iddah maintenance. These irregularities arise from the lack of a clear distinction between the ta‘abbudi dimension, which is fixed and ritual in nature, and the ta‘aqquli dimension, which is rational and contextual, in understanding this legal provision. This study employs a normative legal research method using statutory, conceptual, historical, and comparative approaches. The findings indicate that the obligation of iddah maintenance is grounded in a ta‘abbudi dimension derived directly from the Qur’anic and Prophetic texts. Nevertheless, the form, amount, and mechanism of its fulfillment fall within the ta‘aqquli domain, determined by the husband’s economic capacity, the wife’s reasonable needs, and prevailing socio-economic conditions. An examination of classical fiqh reveals methodological diversity, in which the Hanafi and Maliki schools emphasize maslahah and the protection of women, while the Shafi‘i and Hanbali schools adopt a more textualist and restrictive approach. Judicial practice in Indonesian Religious Courts demonstrates a growing tendency to employ maqāṣid-based reasoning, particularly with regard to the protection of life (ḥifẓ al-nafs), property (ḥifẓ al-māl), and the principle of al-ma‘rūf. This study concludes that iddah maintenance constitutes a hybrid legal norm whose obligation is fixed, while its implementation is context-dependent, and therefore recommends the formulation of more comprehensive judicial guidelines.